The structure of money markets - WILSON, J.S.G. (PSL Quarterly Review, 2014)
The article surveys the main characteristics of money markets. It defines a money market as a centre in which financial institutions congregate for the purpose of dealing in monetary assets. The author stresses the variety of organizational forms as well as the common elements of these markets. JEL: E40, E44, G10, G20